2017
DOI: 10.1007/s10479-017-2676-z
|View full text |Cite
|
Sign up to set email alerts
|

Swift trust and commitment: The missing links for humanitarian supply chain coordination?

Abstract: Coordination among actors in a humanitarian relief supply chain decides whether a relief operation can be or successful or not. In humanitarian supply chains, due to the urgency and importance of the situation combined with scarce resources, actors have to coordinate and trust each other in order to achieve joint goals. This paper investigated empirically the role of swift trust as mediating variable for achieving supply chain coordination. Based on commitment-trust theory we explore enablers of swift-trust an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(170 citation statements)
references
References 86 publications
10
160
0
Order By: Relevance
“…The following Table 2 has illustrated the relations of the aforementioned problems, categorized into ten groups, with eight areas supply chain parameters. Literature was also reviewed (Dubey et al 2017a;Dwivedi et al 2017;Jabbour et al 2017a;Kovács and Spens 2011;McLachlin and Larson 2011;Maon et al 2009) to examine and reveal the causal effects of these problems with the supply chain parameters. It is identified that all the individual problems are related to several areas of parameters.…”
Section: Results Interpretation Discussion and Managerial Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The following Table 2 has illustrated the relations of the aforementioned problems, categorized into ten groups, with eight areas supply chain parameters. Literature was also reviewed (Dubey et al 2017a;Dwivedi et al 2017;Jabbour et al 2017a;Kovács and Spens 2011;McLachlin and Larson 2011;Maon et al 2009) to examine and reveal the causal effects of these problems with the supply chain parameters. It is identified that all the individual problems are related to several areas of parameters.…”
Section: Results Interpretation Discussion and Managerial Implicationmentioning
confidence: 99%
“…On the other hand, since Bangladesh is a developing country, its ability to meet these urgent requirements through designing an efficient supply chain is very problematic. Considering the primary strategic drivers (parameters of supply chain performance) of a supply chain network, existing studies (Allevi et al 2018;Dubey et al 2017a;Georgiadis and Besiou 2008;Surana et al 2005;Whybark et al 2010;Xu and Beamon 2006) have identified many problems in facilities, inventory, transportation, information, sourcing, and pricing, while managing supply chain during emergencies in Bangladesh. Particularly, the Bangladeshi emergency supply chain experiences some traditional problems in planning, forecasting, procurement, storage and inventory management, and distribution (Dwivedi et al 2017).…”
Section: Existing Studies Have Inadequately Explored the Communicatiomentioning
confidence: 99%
“…In addition, Day et al (2012) found that humanitarian supply chain coordination is often a matter of life or death, while effective coordination in traditional consumer goods supply chains is a matter of profit or loss. Finally, in humanitarian supply chains, there is increased reliance on partnering among independent parties who may have no prior working relationship (Dubey et al 2017;Venkatesh et al 2018). Given the pressures and uncertainty with migrant networks, organizations need to focus on managing these unique supply chain constraints to ensure high levels of agility.…”
Section: Dynamic Pressures In Migration Networkmentioning
confidence: 99%
“…As a result, the number of refugees has doubled since 2011; it is estimated that more than 65 million people have been forced to move due to conflict, persecution, or human rights violations (UNHCR 2016). The resulting humanitarian and migration supply chains have correspondingly grown in scale and complexity (Jabbour et al 2017;Oloruntoba et al 2016;Seifert et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the benchmark was kept under complete rationality [8,26]. However, the only goal was to maximize the overall profitability of the supply chain by determining the optimal order quantity q and sales effort e. Previous studies proved that when decision makers were entirely rational, the equilibrium solutions of Complexity the centralized supply chain were always better than the decentralized behavioral supply chain [27,28]. In order to explore research problems and compare optimal decision variables to the decentralized supply chain with behavioral preference analogs, we assumed that the decision maker was rational in the centralized supply chain.…”
Section: Centralized Supply Chain Modelmentioning
confidence: 99%